2007
DOI: 10.1007/s11065-007-9031-0
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Effects of Methamphetamine: A Critical Review and Meta-analysis

Abstract: This review provides a critical analysis of the central nervous system effects of acute and chronic methamphetamine (MA) use, which is linked to numerous adverse psychosocial, neuropsychiatric, and medical problems. A meta-analysis of the neuropsychological effects of MA abuse/dependence revealed broadly medium effect sizes, showing deficits in episodic memory, executive functions, information processing speed, motor skills, language, and visuoconstructional abilities. The neuropsychological deficits associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
524
4
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 587 publications
(564 citation statements)
references
References 190 publications
31
524
4
5
Order By: Relevance
“…Although a similar trend was observed in the impairment rates for executive functions, this pattern of results suggests that the domain of learning may be more sensitive to both HIV and the combination of HIV and methamphetamine than the domain of executive functions. A previous meta-analysis of human studies found that the domain of learning is the most sensitive to methamphetamine-induced cognitive impairments (Scott et al, 2007). Consistent with these findings, we observed subtle effects in the domain of learning, but not on executive functions.…”
Section: Hiv Disease and Methamphetamine Dependence In Humanssupporting
confidence: 91%
“…Although a similar trend was observed in the impairment rates for executive functions, this pattern of results suggests that the domain of learning may be more sensitive to both HIV and the combination of HIV and methamphetamine than the domain of executive functions. A previous meta-analysis of human studies found that the domain of learning is the most sensitive to methamphetamine-induced cognitive impairments (Scott et al, 2007). Consistent with these findings, we observed subtle effects in the domain of learning, but not on executive functions.…”
Section: Hiv Disease and Methamphetamine Dependence In Humanssupporting
confidence: 91%
“…Behavioral treatments, such as cognitive behavioral therapy, are the principal therapeutic strategy used for MA dependence, but they have only achieved modest success (Lee and Rawson, 2008). One reason for the limited efficacy of such therapeutic interventions may be the cognitive impairments associated with chronic MA abuse (eg, London et al, 2005;Monterosso et al, 2005;Salo et al, 2005;Scott et al, 2007;Simon et al, 2010). These impairments may interfere with behavioral treatment, leading to poor treatment retention and outcome (Vocci, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Amphetamine use has been associated with impulsive, aggressive, antisocial, and, in cases, homicidal behaviour in some studies (Qu'est-ce que le captagon, la drogue des djihadistes 2015; Alabdalla 2005; Sekine et al 2006;Scott et al 2007;Freese et al 2002), especially when used in higher dosages and with longer use (Anglin et al 2000). A study of 1016 amphetamine users reported high levels of psychiatric symptoms, particularly depression and attempted suicide, but also anxiety and psychotic symptoms (Lineberry & Bostwick 2006).…”
Section: In Memoriam: the Victims Of The Paris Attacks Of November 13mentioning
confidence: 99%